"Короткий історичний опис про Малу Росію…" та українська історіографія кінця XVIII ст. - Затилюк, Я.; Арістов, В. (Український історичний журнал, 2021)
Мета статті полягає у проведенні джерелознавчого дослідження та реконструкції культурного контексту твору. Методологія поєднує текстологічний і наратологічний підходи. Загальним методологічним полем є історія уявлень та ідей, а також історія історичної думки. Наукова новизна. «Короткий історичний опис про Малу Росію…» – маловивчена пам’ятка українського історієписання рубежу XVIII–ХІХ ст. Після видання тексту за двома списками О.Бодянським у 1848 р. до нього переважно зверталися у зв’язку з питанням авторства І.Квітки. Новий поштовх до вивчення твору дало віднайдення авторами цієї статті списку, що зберігається у фондах Національного музею історії України і є єдиним доступним на сьогодні рукописом пам’ятки. Висновки. Головним джерелом наративного ядра послужив «Літопис Грабянки». Серед інших джерел оповіді, а також додатків, були тексти Ґ.Баєра, Ф.Страленберґа, Феофана (Прокоповича), Антонія Катіфора, Ґ.Міллера. Автор осмислено вибирав і «переплавляв» повідомлення з інших творів, вибудовуючи власну версію козацької історії. Текст з’явився 1789 р., у час розформування структур Гетьманщини і Слобожанщини, коли козацькі «чини» були змушені доводити свою належність до «благородного стану». Він відобразив погляди людей цього середовища та засвідчив їхню ориґінальну спробу переосмислити традиційний наратив «Літопису Грабянки» й модифікувати усталену схему козацького минулого. Відповідальність за обмеження прав Малої Росії покладалася на гетьманів. У неґативних тонах представлено також запорожців. З аналізу контексту постання та побутування пам’ятки випливає, що її було створено в колах, близьких до старшинських родин Квіток, Горленків, інших «патріотів краю». Твір належить до останньої хвилі так званої козацької історіографії і є віддаленим попередником «Історії русів». The aim of the article is the source study of the A Brief Historical Description of Little Russia… and the reconstruction of its cultural context. The methodology of the study combines the text-critical and narratological approaches to the analysis of the text. The general methodological field of the article is history of ideas and history of historical thought. Scientific novelty. A Brief Historical Description of Little Russia… is a text of Ukrainian historiography of the late 18th century which has not been fully studied. After the publication of the text on the basis of two copies by O.Bodianskyi in 1848, it was mostly approached in connection with the question of I.Kvitka’s authorship. A new impetus to the study of the work was given by the discovery of its copy by the article’s authors which was stored in the National Museum of the History of Ukraine. This is the only available manuscript of the work. Conclusions. The main source of the work’s narrative core was the Hrabianka Chronicle. Other sources of the narrative, as well as the appendices, included the works by G.Bayer, Ph.Stralenberg, Feofan (Prokopovych), Anthony Katifor, and G.Müller. The author deliberately selected and “melted” the information from other works, building up his own version of the Cossack history. The work was written in 1789, at the time of the disintegration of the structures of the Hetmanshchyna and Sloboda Ukraine, when the Cossack “ranks” were forced to prove their belonging to the “noble class”. It reflected the views of the people of this environment and testified to their original attempt to rethink the traditional narrative of the Hrabianka Chronicle and modify the established scheme of the Cossack past. The responsibility for restricting the rights of Little Russia in this work rests with the hetmans. The Zaporozhians are also presented in negative tones. The analysis of the context of the creation and history of the work suggests that it was created in the circles close to the starshyna families of Kvitka, Horlenko and other “patriots of the region”. A Brief Historical Description of Little Russia… belongs to the last generation of the Cossack historiography and is a distant predecessor of the History of Ruthenians.